The woman from Lydia [large type] - Hunt, Angela Elwell, 1957- (Hunt, Angela Elwell, 1957- Emissaries, 2023)
"Widowed Euodia, known to her neighbors as "the Lydian woman," seeks to make a fresh start by moving to the foreign city of Philippi. She finds new purpose after meeting Paulos, apostle to the Gentiles, who opens her eyes to helping those in need, particularly women and those who have been enslaved. Retired Roman soldier Hector has settled in Philippi with dreams of a future filled with wealth and status, pooling his army earnings with Lucius, his fellow comrade in arms turned business partner. His hopes are dashed, however, when Paulos robs their youngest slave of her lucrative ability to foretell the future, rendering her worthless to Hector's ambition. When Euodia becomes aware that Sabina is being mistreated, she buys Sabina from Lucius, intending to set the girl free. But when Hector claims the sale was not legitimate, he takes Sabina back and swears he will find someone to restore her valuable "gift" . . . even if he must travel to the ends of the earth to do so. Following close behind him, Euodia and her servants set out to rescue Sabina, not for gain, but to set her free forever"--